2016
DOI: 10.1016/j.clnesp.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

An initial evaluation of newly proposed biomarker of zinc status in humans - linoleic acid: dihomo-γ-linolenic acid (LA:DGLA) ratio

Abstract: This study is an initial step in evaluating LA: DGLA ratio as a biomarker of Zn status in humans. The results are encouraging as they show that concentration of DGLA is decreased and LA: DGLA ratio increased in people with lower dietary Zn intake. However, additional studies are needed to fully examine the sensitivity of this biomarker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 53 publications
6
40
0
Order By: Relevance
“…As with earlier findings [80,81] in our study no relationships were found between the statuses of trace elements with age. The increasing concentration of plasma Zn was associated with higher BMI and weight, similar to previous reports [33,82,83]. Yu et al [61] reported comparable results in metabolic syndrome patients, higher serum Zn levels in those with higher weight.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…As with earlier findings [80,81] in our study no relationships were found between the statuses of trace elements with age. The increasing concentration of plasma Zn was associated with higher BMI and weight, similar to previous reports [33,82,83]. Yu et al [61] reported comparable results in metabolic syndrome patients, higher serum Zn levels in those with higher weight.…”
Section: Discussionsupporting
confidence: 87%
“…The low plasma Zn concentrations were also seen in obese individuals, those with hypertension and type 2 diabetes [57,58]. Fe and Cu status data were within the estimated reference ranges for adult population, and similar to the values reported elsewhere [33,59]. The highest concentrations of Cu were seen in people with the lowest levels of plasma Zn.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations